Pelatihan Teknik Fotografi Produk Berbasis Low-Cost Equipment untuk Mendukung Pemasaran Digital UMKM Desa Kroya - Solichah Larasati; Indah Permatasari; Gusnita Linda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Small and Medium Enterprises (SMEs) in Kroya Village have considerable product potential; however, they still face challenges in digital marketing, particularly in terms of product photo visual quality. The main issues include limited product photography skills and the perception that producing attractive product photos requires expensive equipment. This community service program aims to enhance the capacity of MSME actors in Kroya Village to produce visually appropriate product photos through training in product photography techniques using low-cost equipment. The program employed a participatory and applicative approach, including problem identification, learning-by-doing training sessions, as well as mentoring and evaluation. The training involved 30 MSME participants and utilized simple equipment such as product photo boxes and LED lighting. The results indicate an improvement in product photo quality in terms of lighting, object sharpness, composition, and background suitability, making the photos more suitable for digital marketing purposes. This program contributes to strengthening MSME independence in managing visual marketing content.